Makna Dibalik Iklan Kampanye Prabowo Gibran Versi Generasi Sehat Indonesia Maju di Media Sosial - Intan Nurul Azzahra; Arfian Suryasuciramdhan; Intan Inayah; Aliya Dwi Rahayu Putri; Reyhan Naufal Athaya (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
In political contests, campaign visuals play a significant role in shaping public perceptions of candidates. Campaign advertisements often do not only convey messages explicitly, but also embed symbolic meanings through visual and audio elements. The problem addressed in this study lies in how visual propaganda is strategically employed in the Prabowo-Gibran campaign advertisement titled Generasi Sehat Indonesia Maju to construct a positive image of the candidate pair through the representation of children and symbols of health. This study aims to examine the use of visual and audio elements in building a political narrative that appeals to both emotional and symbolic aspects. Using a qualitative method with a content analysis approach, the research explores visual representations of healthy and joyful children, the symbolism of milk as a health icon, and the portrayal of the main figures as close to family values. The findings indicate that the visual propaganda in this advertisement effectively communicates the campaign's message by establishing a positive association with the candidates through elements of togetherness, concern for children's nutrition, and hope for a better future. In conclusion, the advertisement utilizes visual propaganda to foster the perception that the Prabowo-Gibran pair are leaders who genuinely care about the younger generation and the well-being of Indonesian families.